Child's Lineage Al-Li'an (Oath of Condemnation) and his Inheritance Rights: A Comparative Study Between Islamic and Malaysian Law - Azziz Raouane; Ruhi Fadzlyana Jailani; Mualimin Mochammad Sahid; Mushaddad Hasbullah (USIM Press, 2024)
The lineage of al-li`an child and his inheritance from his father, who denied him and performed oath of condemnation (al-mula’anah) is considered one of the crucial issues in the Sharia and the law. This is because of the serious effects of denying his lineage from his father, which leads to depriving the child of the inheritance of the father and his family. Some courts accepted the analysis of the DNA when denying the child's lineage. Based on this fact, the issue has raised, especially when there is a conflict between the father’s denial of his son and the court’s finding based on DNA result. Which one is to be accepted if the father denied while the court confirmed his child’s lineage? This study aimed at introducing al-li`an child from Sharia and legal points of view, and the importance of analyzing the genetic footprint (DNA) as a guide to be used when there is a conflict between husband and wife in their opinions. The research methods used in this study are the inductive approach by tracking the views and evidence of the Islamic jurists and examining the reasons for the disagreement among them. In comparison, the analytical and comparative methods are used to discuss and analyze the opinions of the jurists and their evidence and compare these provisions with what is being practiced in Malaysian law. This study has reached some important results among others: the child of al-li`an remains a legitimate child as long as the father did not deny his lineage. The final decision on denying or confirming child’s lineage is based on the analysis of the genetic fingerprint (DNA result). Therefore, the lineage of al-li’an child and his inheritance right remains valid or undeniable unless the analysis result of the genetic fingerprint conforms with the statement of the father who denied his child lineage through al-li`an (oath of condemnation).